Avaliação da percepção nociceptiva em indivíduos com síndrome de Moebius - Accurso, Selma Redis (2018)
Individuals with Moebius syndrome (MS) have sensory alterations caused by involvement of the seventh cranial nerve in this neurological disorder. Such impairment can cause difficulties during speech and chewing, as well as facial weakness, among others. The innervation compromised by MS may also include other mixed (motor and sensitive) nerves of the orofacial region. There is no report in the literature that investigated the perception of pain threshold in masticatory muscles in individuals with MS. Objective: The aim of this study was to evaluate the pain threshold in masticatory muscles as well as the frequency of TMD signs and symptoms in MS individuals and to compare them with normoreactive individuals. Materials and methods: For this purpose, 40 participants were evaluated, divided into 2 groups. Group 1 (GE), containing 20 subjects with MS and group 2 (CG), containing 20 normoreactive individuals. The pain evaluation was performed using a pressure algometer and the evaluation of the signs and symptoms of temporomandibular disorders was made according to Diagnostic Criteria for Temporomandibular Disorders (DC / TMD) and a visual analogue scale. Results: The pain threshold in the temporal, right and left temporal muscles, was higher in G1, compared to G2 (p <0.05). The mean pressure rate was lower in the G2, compared to the G1 (p> 0.05) and the examination time was higher for the study group, both for the temporal and masseter muscle (p <0.05). The pain thresholds in these two muscle groups were similar in both right and left sides in patients with MS. None of the findings were enough to make a positive diagnosis of TMD or in G1 as in G2. Regarding the signs and symptoms of TMD, the G1 showed a higher frequency of articular sound (p = 0.017) and limitation of mouth opening (p <0.001). In the investigation of frequency of parafunctional habits, the CG had a higher index (p= 0.022). Conclusion: Individuals with MS have lower nociceptive perception and increased signs and symptoms of TMD when compared to normoreactive ones.